Zakat 4.0: The Role of FinTech and Blockchain Platforms in Optimizing Zakat Collection and Distribution for Poverty Alleviation - Loso Judijanto; Meera Gupta; Murat Atayev; Tolgay Saparov (Yayasan Adra Karima Hubbi, 2025)
The emergence of digital technologies, particularly financial technology (FinTech) and blockchain systems, has transformed the landscape of Islamic social finance, offering new opportunities to strengthen the effectiveness of zakat management in the era of Zakat 4.0. Persistent inefficiencies in conventional zakat collection and distribution—such as limited outreach, administrative delays, and lack of transparency—continue to hinder its potential for sustainable poverty alleviation. The digitalization of zakat institutions presents a promising pathway to enhance accountability, expand access, and ensure that zakat reaches eligible beneficiaries in a timely and equitable manner. This study aims to examine how FinTech and blockchain-based platforms contribute to optimizing zakat collection and distribution within contemporary socio-economic contexts. The research focuses on identifying the technological mechanisms that improve data accuracy, enhance donor trust, streamline verification processes, and support evidence-based targeting of mustahiq populations. The analysis also evaluates how digital platforms align with sharia principles while addressing operational challenges faced by zakat agencies. A mixed-methods approach was employed, combining systematic literature review, analysis of secondary data from digital zakat platforms, and semi-structured interviews with practitioners from zakat institutions in Southeast Asia and the Middle East. Quantitative indicators—such as collection growth, transaction transparency, and distribution efficiency—were triangulated with qualitative insights to produce a comprehensive understanding of digital transformation in zakat management. The findings show that FinTech and blockchain significantly increase zakat collection rates, improve traceability, and reduce administrative leakages through smart contracts and automated reporting. The results suggest that digital zakat systems strengthen institutional credibility and foster greater participation among donors, ultimately enhancing the poverty alleviation impact. The study concludes that Zakat 4.0 represents a transformative model capable of establishing a more transparent, inclusive, and data-driven zakat ecosystem.